Simulação numérica do processo de expansão de stents para angioplastia por hidroconformação - Araújo, Rogério de (2007)
In early times, the cardiovascular diseases were treated by the bypass surgery. Nowadays, these diseases have been treated with a minimally invasive procedure, the percutaneous transluminal coronary angioplasty. In one of these procedures, a metallic tubular device, known as stent, is placed on the catheter with an expandable balloon. The stent is implanted in the region of the obstructed artery, decreasing the possibility of reestenosis. Therefore, a successfully angioplasty depends on the knowing of the expansion process. In this context, the finite elements method can be used as a tool of analysis of the performance of a stent implanted on the arterial wall. Because of the similarity between the angioplasty process and the tube hydroforming, the tube hydroforming simulation by finite element method was used in this work to study the behavior of the two stent models topologically optimized by Guimarães (2005). The same procedure was also used in the simulation of the expansion of a commercial stent model and the results were compared with the stents studied by Guimarães (2005). The stent expansion process simulation was carried out using the software Stampack®. From the results, it was possible to predict some design parameters, such as, the pressure of expansion of the balloon, the plastic strain field in the stent, the relative thickness and the springback.